Interpersonal Collaboration to Support Digitally Mediated Gig Workers’ Well-being in Pre- and Post-Pandemic Times - Wang, Hao-Chuan; You, Chuang-Wen; Yuan, Chien-Wen; Bi, Nanyi; Cherng, Fu-Yin (2020)
ABSTRACT The COVID-19 outbreak has raised concerns about its impact on gig workers, who perform on-demand flexible work that is mediated by digital work platforms (e.g., Uber and DoorDash), in terms of their safety, health, and well-being. The situation facing gig workers is also closely related to the public as the demand for the services provided by them has increased dramatically. However, the need for better supporting gig workers’ well-being and work-life balance is not new. Issues such as lack of self-awareness about personal health conditions or uncontrolled long working hours tend to be common among workers. Given the flexibility of gig work, it remains unclear what mechanisms or interventions may improve the well-being awareness and practices of workers. In this short paper, we discuss the potential may serve to fostering health collaboration between the workers and their significant others (e.g., family members) through technological medications. We present a pre-pandemic case study that deploys a social sensing mobile app to Uber and taxi drivers and their partners for a month. The app allows a partner to access a worker’s health sensing data, add interpersonal observations about the worker’s wellness, and participate in the process of their well-being management. We reflect on what we learned from this pre-pandemic study in order to shed light on ways to support well-being management for gig workers in the current and post-pandemic times. Key Words gig workers, work-life balance, well-being, health sensing, collaborative health management, computer-supported collaboration, sharing economy ABOUT THE AUTHOR/S Hao-Chuan Wang UC Davis hciwang@ucdavis.edu Hao-Chuan Wang is an acting Associate Professor in the Department of Computer Science, University of California, Davis. He studies how computer-mediated communication tools can be shaped to address collaborative and societal issues, such as bridging cultural and language gaps between global co-workers, and support expert-novice knowledge transfer to ensure the wellness and sustainability of work practices in platform and gig economies. Personal website: http://www.haochuanwang.info/ Chuang-Wen You National Tsing Hua University cwyou@mx.nthu.edu.tw Chien-Wen Yuan National Taiwan Normal University tinayuan@ntnu.edu.tw Nanyi Bi National Taiwan University nanyi.bi@gmail.com Fu-Yin Cherng UC Davis fuyincherng@gmail.com New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).